Edukasi dan Pendampingan Pencegahan Stunting melalui Optimalisasi Pekarangan Pangan Lestari bagi Ibu Rumah Tangga di Kabupaten Timor Tengah Selatan, Nusa Tenggara Timur - Maria Ratu Sika; Gertruda Lopo Dhena (UNITY: Journal of Community Service, 2026)
Stunting remains a major public health challenge in Indonesia, particularly in areas with limited access to nutritious food and low utilization of local food resources. Timor Tengah Selatan Regency, East Nusa Tenggara, is one of the regions facing challenges in fulfilling family nutrition due to economic constraints, dietary patterns, and limited household food diversification. This community service program aimed to improve the knowledge and skills of housewives in preventing stunting through the optimization of Sustainable Food Yard (Pekarangan Pangan Lestari/P2L) as a source of nutritious family food. The implementation methods included initial assessment, education on stunting and balanced nutrition, training on yard utilization, practical cultivation of food crops and vegetables, and continuous assistance in managing household food production. The results showed an improvement in participants' understanding of the relationship between food availability, nutrition, and stunting prevention. Participants were also able to implement simple yard management practices to provide more diverse and nutritious family food sources. This program demonstrates that household-based empowerment through sustainable food yard optimization can support family food security and serve as a preventive strategy to reduce stunting risks in rural communities.